2017
DOI: 10.1002/jrs.5113
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of the quantification of respirable crystalline silica by mass on aerosol sampling filters using Raman microscopy

Abstract: Airborne respirable crystalline silica (RCS) is a hazard that can affect the health of workers, and more sensitive measurements are needed for the assessment of worker exposure. To assess the use of Raman microscopy for the analysis of RCS particulate collected on filters, aliquots of quartz or cristobalite suspended in isopropanol were pipetted onto silver filters. Samples were measured by arbitrarily selecting positions along the filter and collecting spectra at 50 discrete points. The calculated limits of q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…This method also offers the ability to pretreat filter samples to minimize matrix interferences (for example, following protocols outlined in ASTM D7948); however such pretratment may increase detection limits beyond 0.3 μg . While recent studies 9 , 10 have shown that new FTIR and Raman instrumentation can provide similar LODs reported here, QCL-based spectrometers offer unique advantages with respect to development of compact, hand-portable, near real-time aerosol sensors.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…This method also offers the ability to pretreat filter samples to minimize matrix interferences (for example, following protocols outlined in ASTM D7948); however such pretratment may increase detection limits beyond 0.3 μg . While recent studies 9 , 10 have shown that new FTIR and Raman instrumentation can provide similar LODs reported here, QCL-based spectrometers offer unique advantages with respect to development of compact, hand-portable, near real-time aerosol sensors.…”
Section: Discussionsupporting
confidence: 52%
“…Estimated method detection limits (MDLs) for RCS by XRD and IR range from 1 to >10 μg per sample 7 , 8 . Recent studies using new FTIR instrumentation 9 and Raman microscopy 10 have demonstrated LODs below 1 μg . In consideration of lower occupational exposure limits (OELs), better MDLs are desired.…”
Section: Introductionmentioning
confidence: 99%
“…Measurement conditions were based on those described in a feasibility study using 5 mm diameter deposit area. 11 An In-Via Raman microscope (Renishaw Ltd, Gloucester, UK) with near infrared laser (785 nm) excitation, CCD camera, and a grating with 1200 l mm À1 was used to collect Raman spectra between 314 and 906 cm À1 . This range was set to avoid the broad Raman band below 300 cm À1 , which was attributed to a trace of silver oxide.…”
Section: Calibration and Raman Measurement Conditionsmentioning
confidence: 99%
“…Airborne RCS is a hazard that can affect the health of workers, and more sensitive measurements are needed for the assessment of worker exposure. Their data show that Raman spectroscopy is a viable option for the quantification of the mass of RSC on filters with a limit of detection approaching one‐tenth of that obtained with other techniques . Taddei, Pavoni, and Affatato carried out a comparative micro‐Raman study on standard, cross‐linked, and vitamin E‐blended polyethylene acetabular cups after long‐term in vitro testing and ageing.…”
Section: Biosciencesmentioning
confidence: 99%
“…Their data show that Raman spectroscopy is a viable option for the quantification of the mass of RSC on filters with a limit of detection approaching one-tenth of that obtained with other techniques. [73] Taddei, Pavoni, and Affatato carried out a comparative micro-Raman study on standard, cross-linked, and vitamin E-blended polyethylene acetabular cups after long-term in vitro testing and ageing. Micro-Raman spectroscopy allowed them to analyze the wear degradation of the cups on a molecular scale, and as a result, differences in the wear mechanisms were revealed.…”
Section: Medical and Biomedical Applications Tissues Plants And mentioning
confidence: 99%